Exegetical Teaching on the Concept “Μακάριοσ” Based on the Book of Revelation - Marthen Mau (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
Many individuals, including those who profess faith, often struggle to endure the various forms of suffering encountered in life, primarily because it is difficult for human beings to accept pain and trials as part of their earthly journey. As a result, some fail to attain the promise of eternal happiness at the culmination of their lives. According to the Christian faith, true and lasting happiness is not achieved through worldly comfort but is reserved only for those who consistently read and meditate on the Scriptures, whether privately or in communal settings, who strive to preserve holiness in their daily lives, who remain faithful in following Jesus even until death, and who demonstrate obedience to God’s Word. Such believers will not experience eternal death but are granted the privilege to enter the holy city and participate in the joyous banquet of Christ. The purpose of this research is to explore the pathway toward attaining genuine happiness, both in earthly life and ultimately in the holy city of God, which requires a willingness to endure even physical suffering, potentially unto death. To ensure reliable findings, the study employs a qualitative methodology with a grammatical-textual approach combined with interviews. The findings indicate that believers who comprehend the meaning of the Greek concept “μακάριος” (makarios) as it appears in the Book of Revelation will gain firm confidence to endure suffering, maintaining faith and perseverance, even if that perseverance leads to martyrdom for the sake of Christ Jesus.